Perlindungan Hukum Terhadap Pekerja Seks Komersil Anak Di Kabupaten Kepulauan Aru - Zeti Utami; Hadibah Zachra Wadjo (SANISA: Jurnal Kreativitas Mahasiswa Hukum, 2021)
Introductioan: Protection provided by Law Number 35 of 2014 in Article 68, namely legal protection for children of special commercial sex workers is carried out through efforts of supervision, protection, prevention, care and rehabilitation as well as legal assistance.Purposes of the Research: This study aims to analyze and discuss the form of legal protection for child commercial sex workers in Aru Islands Regency. Methods of the Research: The research method used is normative juridical research. The type of research is descriptive analytical. The source of legal materials is primary and secondary legal materials. The collection technique is through library research and further analyzed by means of descriptions using qualitative methods. Based on the results and discussion. Results of the Research: Legal protection for Child Commercial Sex Workers that has been carried out by the government in the Aru Islands by providing assistance for child commercial sex workers by the Office of Women's Empowerment and Child Protection in the form of medical assistance and psychological assistance. However, legal protection for child commercial sex workers has not been maximized as mandated by law, this can be seen from the form of legal protection provided to child victims of commercial sex workers in the Aru Islands, only limited to assistance by the Office of Women's Empowerment and Child Protection in the Aru Islands. in the investigation stage, this is due to a lack of synergy between legal protection institutions and the absence of a legal umbrella in the form of Regional Regulations in the Aru Islands.